Prioritizing competencies for soldier’s mental resilience: an application of integrative fuzzy-trapezoidal decision-making trial and evaluation laboratory in updating training program - Bekesiene, Svajone; Smaliukienė, Rasa; Vaičaitienė, Ramutė; Bagdžiūnienė, Dalia; Kanapeckaitė, Rosita; Kapustian, Olena; Nakonechnyi, Oleksandr (Frontiers in Psychology, 2024)
With the current geopolitical landscape and ongoing military conflicts in Europe, it is necessary to expedite training of soldiers, including resilience training, without compromising the effectiveness of the program. This study aims to address this research gap by using a reductionist approach to resilience training and identifying the critical competencies that senior soldiers need to be trained to coach younger soldiers to maintain psychological strength during deployment. By filling this research gap, the study will contribute to the development of more efficient and targeted resilience training programs that optimize the ability of soldiers to adapt and excel in challenging military environments. To address the issue, this study assessed the competencies comprising the Master Resilience Training (MRT) program, widely recognized as one of the most effective military resilience training programs. Two groups of military experts, totaling 16 individuals, were involved in the evaluation process, representing two military contexts. The assessment of resilience competencies was carried out using a deep analysis approach through the application of effective multi-criteria decision-making (MCDM). Specifically, the Decision-making Trial and Evaluation Laboratory (DEMATEL) method was used. In this study, the DEMATEL model was extended using trapezoidal fuzzy numbers (TrFN-DEMATEL) to accommodate decision-making under uncertainty conditions. The research findings highlight the critical importance of three core resilience competencies: self-regulation, mental agility, and strength of character. The importance of each competency varies depending on the specific military context. When defending one's own country's territory, strength of character emerges as the key factor in enhancing soldiers' mental resilience. Conversely, during military operations abroad, self-regulation is the primary factor that promotes psychological resilience. Furthermore, the results show that these three primary competencies form a 'cause group' that influences other competencies through a cause-and-effect dependency. Conclusions: Based on the findings, the theoretical conclusion is drawn that the importance of resilience competencies is contextually differentiated. Furthermore, each resilience competency is associated with a set of causes or effects. These are valuable insights for improving resilience competency training programs.